The Application Offthe Think-Pair-Share Learninggmodel To The Study Of Algebraic Fractions In Mathematics - Ruslan Mantiaha; Jorry F. Monoarfa; Murni Sulistyaningsih (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
The objective offthis study is to assess the impact of the Think-Pair-Share (TPS) cooperativeelearning modelron the mathematical development of students. This method of investigation is quasi-experimental. This study included students from both seventh grades at SMP Negeri 4 Tabukan Utara. The data was obtained from a test designed to assess understanding of Algebraic Fractions. Class analysis results for the Think Pair ShareeCooperative learninggmodel class and the direct learning model class indicate that the average learninggoutcomes of studentsstaught utilizing the ThinkkPairrShare Cooperativeelearning modelaare greater than those of studentsstaught utilizing the direct learning model.